Pengaruh Jenis Pakan PENGARUH PEMBERIAN JENIS PAKAN TERHADAP KUALITAS REPRODUKSI IKAN PLATY PEDANG: Untuk mengetahui pengaruh perbedaan pemberian jenis pakan terhadap kualitas reproduksi yang dihasilkan oleh induk ikan betina - Tanjung, Rika Muliana; Angkat, Hafsah Nanda Kirana (Program Studi Budidaya Perairan Universitas Mataram, 2023)
Ornamental sword platy fish is a type of ornamental fish that has high economic value. This is supported by the large number of fans of ornamental sword platy fish which are not only limited to the high economic class, but also the marginalized, from children, teenagers to adults. This research was carried out for 2 weeks in November 2022 on Jl. Chief no. 3c Downstream Ape Sei I. The method used in this mini-research was a qualitative method. Based on the results of the observation that the research shows that the productivity of fish eggs is faster if the fish are fed silk worms compared to pellet feed. Feed greatly affects the reproductive quality of sword platyfish because what is eaten should have a direct impact on the health of the body, including that of animals.